2003
DOI: 10.1177/002215540305100103
|View full text |Cite
|
Sign up to set email alerts
|

Detection of PrPsc in Samples Presenting a Very Advanced Degree of Autolysis (BSE Liquid State) by Immunocytochemistry

Abstract: S U M M A R YAlthough detection of the abnormal isoform of prion protein (PrP sc ), the specific feature of transmissable spongiform encephalopathies (TSEs), has been previously demonstrated on formalin-fixed autolytic tissue, no samples with autolysis as severe as tested here (i.e., liquid state) have previously been tested. It is inevitable that a small but significant proportion of brains, especially in summer due to delays in postmortem examination, undergo an extremely severe autolysis that makes samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…However, optimal preservation is required to ensure the identification of vacuolar changes in certain areas of the brainstem devoid of artifactual vacuolations induced by a postmortem delay of tissue sampling that led to autolysis. Although autolysis conditions have been usually encountered in field cases of BSE diagnosis, autolysis and the frozen condition do not significantly influence PrP Sc detection by immunohistochemistry [4,6,7,18]. Moreover, PrP Sc immunohistochemistry is an essential tool and may contribute to our understanding of the pathogenesis of BSE [6,12].…”
Section: Discussionmentioning
confidence: 99%
“…However, optimal preservation is required to ensure the identification of vacuolar changes in certain areas of the brainstem devoid of artifactual vacuolations induced by a postmortem delay of tissue sampling that led to autolysis. Although autolysis conditions have been usually encountered in field cases of BSE diagnosis, autolysis and the frozen condition do not significantly influence PrP Sc detection by immunohistochemistry [4,6,7,18]. Moreover, PrP Sc immunohistochemistry is an essential tool and may contribute to our understanding of the pathogenesis of BSE [6,12].…”
Section: Discussionmentioning
confidence: 99%
“…However, it has largely been concluded that autolysis does not compromise the accuracy of assays that detect the proteinase-resistant, pathogenic isoform of the prion protein (PrP res ). 2,5,7,8,12,16 It was hypothesized that over a relatively long period of time, exposure to heat may have a more substantial effect on PrP res immunodection than previously considered. The objective of the present study was to characterize PrP CWD detectability with time in brain samples subjected to heat in vitro as determined by Western blot.…”
mentioning
confidence: 99%
“…Monle ó n et al 72 documented an interesting IHC result of detecting the abnormal isoform of prion protein (PrP sc ) in cattle brain tissues that had been subjected to very advanced autolysis (liquid state) using the AR treatment. They took the liquid -like animal brain tissue by a swab, and made smear onto Vectabond (Vector Laboratories, Burlingame, CA) -pretreated glass slides after dilution of the liquid tissue, followed by drying at 56 ° C for 24 h, and fi xed in 10% formalin for 1 h .…”
Section: Ar Used For Tissue Samples Subject To Autolysismentioning
confidence: 99%